2014
DOI: 10.1902/jop.2014.140135
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Aggressive Periodontitis as a Risk Factor for Dental Implant Failure: A Systematic Review and Meta‐Analysis

Abstract: Implant placement in patients with a history of GAgP might be considered a viable option to restore oral function with survival outcomes similar to those found in both patients with CP and HPs. However, the risk ratio for failure in patients with AgP is significantly higher when compared with HPs (4.0) and those with CP (3.97).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…Monje et al. () calculated that the risk ratio for implant failures in patients with aggressive periodontitis was significantly higher when compared with patients without a history of periodontitis (4.0) and those with chronic periodontitis (3.97).…”
Section: Discussionmentioning
confidence: 99%
“…Monje et al. () calculated that the risk ratio for implant failures in patients with aggressive periodontitis was significantly higher when compared with patients without a history of periodontitis (4.0) and those with chronic periodontitis (3.97).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mucositis and peri‐implantitis affecting implants supporting overdentures have been reported 8 . It has been suggested that patients with a history of generalized aggressive periodontitis are more susceptible to mucositis and peri‐implantitis 9 . Bone loss associated with peri‐implantitis could be the cause of peri‐implant gingival recession.…”
Section: Discussionmentioning
confidence: 99%
“…8 It has been suggested that patients with a history of generalized aggressive periodontitis are more susceptible to mucositis and peri-implantitis. 9 Bone loss associated with peri-implantitis could be the cause of peri-implant gingival recession. Peri-implantitis has been categorized as early, moderate, and advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral hygiene, history of periodontitis and smoking has been considered as risk factors at the Sixth European Workshop on Periodontology . Monje et al . have stated that survival rate of dental implants in aggressive periodontitis is similar to those in chronic periodontitis and healthy controls, however success rate of implants is lower in patients with aggressive periodontitis than those of chronic periodontitis and controls.…”
Section: Introductionmentioning
confidence: 99%